How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

The power of will and choice of law in international contracts - Dazzi, Pietro Giulio (LUISS Guido Carli, 2019)
Party autonomy and sovereignty. Historical developments on party autonomy, the evolution of choice of law. The freedom of choice. The freedom not to choose, absence of choice. Limits to the freedom of choice. Limits to the freedom of choice, an expression of sovereignty. Same functions, different results.

A critical analysis of the effectiveness of the business rescue regime as a mechanism for corporate rescue - Bagwandeen, Kiren Kesh (University of KwaZulu-Natal, 2019)
Almost eight years after the enactment of the business rescue regime under the Companies Act 71 of 2008, and a plethora of judgments which have probed and prodded its provisions, it is an opportune time to ascertain whether the business rescue regime is an effective corporate rescue mechanism suitable to the modern day demands of the South African economy. In the current economic downturn, South Africa can ill afford a repeat show of the failed judicial management system. It requires a modern and effective corporate rescue mechanism that can be utilised in appropriate circumstances as a viable alternative and not merely a precursor to liquidation. This dissertation seeks to provide a critical analysis of the effectiveness of the business rescue regime to ascertain its worthiness as a corporate rescue mechanism.
Keywords: Bankruptcy; Business failures; Corporation law; Insolvency; South Africa

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

The models of attribution in the establishment of corporate liability revisited - Heese, Francisca Alida (Stellenbosch University, 2019)
The separate legal personality of a company is one of the cornerstones of modern corporate law. Nevertheless, due to the artificial nature of a company it has no inherent moral blameworthiness necessary to impose corporate liability. With a rise in corporate wrongdoing, there is a need to hold companies liable. Therefore, certain models of attribution have developed whereby the conduct and will of a corporate actor can be imputed to the company to establish corporate liability. Especially in the realm of corporate criminal liability, these models of attribution have played a pivotal role to establish corporate wrongdoing. The two broad theories underlying the models of attribution are the fiction and realist theories respectively. The directing minds doctrine or identification doctrine and the vicarious liability model are traditionally associated with the fiction theory, which is rooted in the abstract nature of a company. Whether the traditional models of attribution are suited for complex modern organisational structures, is explored in this thesis, whilst a more functional and realistic approach to corporate liability is proposed. Often the question of “what is a corporation” has overshadowed the determination of corporate liability, thus a more contextual analysis based on law and economics is proposed to ensure corporate liability. The development of the rules of attribution through case law illustrate the importance of a purposive approach to establishing corporate liability. Furthermore, the underlying relationship between the rules of attribution and the rules of agency indicate that the interests of risk-bearers and managers are not always aligned and should be redressed. Moreover, a realist approach as opposed to the fictional approach to attribution has been developed in English and Australian law. This approach focuses on the overarching corporate culture and identity when determining corporate fault, instead of individual corporate actors. These regulatory frameworks provide an alternative approach to the current South African model, which is based on the fiction theory. Lastly, the economic considerations, such as the separation of ownership and control and the agency problem, are evaluated to determine whether the current models of attribution create an economically efficient outcome or an unsustainable a risk-taking environment.
Keywords: Corporate culture; Corporate liability; Corporation law

Choice of law in International Commercial contracts in the BRICS countries - Agbeko, Fafa Delight (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Rethinking international employment contracts in the wake of the Fourth Industrial Revolution - Antwi-Larbi, Nana Amobea (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

Choice of forum in International Commercial Contracts : a comparison of the position in Ghana and under the Brussels IBIS regulation - Asante-Aboagye, Benedicta (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Belgium; Border trade; Conflict of laws; Ghana; International commercial contracts; Litigation

The treatment and recognition of company groups in South African corporate law - Diale-Ali, Regomoditswe Ursula (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

A critical appraisal of call centre contracts for insurance - Dladla, Mbongeni George (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

The role of the Hague principles on choice of law in international commercial contracts in Japanese private international law - Geraghty, Brandon Brian (University of Johannesburg, 2019)
Please refer to full text to view abstract LL.M. (International Commercial Law)
Keywords: Conflict of laws; Contracts (International law); Japan

A comparative analysis of mergers and acquisitions in South Africa, Botswana and Kenya : how can we achieve successful integration in Africa? - Gumede, Nomfundo Pretty (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Acquisitions; Amalgamation; Bots; Business; Corporate mergers; Integration; Kenya; Mergers; South Africa

The contractual landscape and the protection of consumers in online auction contracts - Khan, Haleema (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Aquilian liability : the best remedy against delinquent company directors - Kharametsane, Godirilwe (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

An analysis of reinstatement as a primary remedy for unfair dismissal of employees in South African Labour Law - Mampholo, Yvonne Mokhubane (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Intermediaries and advisors' duties to disclose onerous clauses to prospective policyholders - Matshitse, Collen Kgaolo Stephen (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Commercial law; Insurance law

The recovery of cultural property in international law: collaborative settlements of disputes - Mauro, Benedetta (LUISS Guido Carli, 2019)

An investigation into the effectiveness of trade unions in advancing the cause of workers during strikes in the face of an emerging culture of violence and criminality - Mfusi, Pearl Dawn Arnold (University of KwaZulu-Natal, 2019)
No abstract available.
Keywords: Labour protests; Liability; Strikes; Trade unions; Violent protests; Violent strikes; Workers

Towards development-centred trade relations: a study of South Africa and the USA trade relations with particular focus on the African Growth and Opportunity Act (AGOA) - Mkhwanazi, Nhlakanipho (University of KwaZulu-Natal, 2019)
With trade taking place continuously on a daily basis, its often-reported success gives the impression that all participants involved are to a certain extent somewhat successful too. This dissertation draws attention to the discrepancies that have often gone unnoticed throughout the decades and the effects that have arisen as a result. South Africa’s (SA) and the United States of America’s (US) trade relationship through the African Growth and Opportunity Act (AGOA) is the focus of this study, with this relationship being analysed from as far back as history has been recorded to the modern day. Least developed countries (LDCs) are an integral part of this study because most trade-related activities involve them, and they contain most of the world’s natural resources, but most importantly they also make up a large portion of the world’s population. It's baffling to see that where these factors are present, there's also inequality. Seemingly, there are efforts that deal specifically with the challenges faced by developing countries, but what is concerning is these solutions are formulated by developed countries which created them and continue to perpetuate them. The approach adopted was mostly that of contrasting events that have involved trade over the decades and a discussion of how these events have shaped international, political and trade relations, that is, the existing status quo. Examples include the two World Wars; oppressive regimes such as apartheid; and the formation of global institutions ranging from the International Trade Organization (ITO) to the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO). The first three chapters contain an introduction, a background focus on development and the history of relations between South Africa and the United States of America. The last two chapters contain a discussion on AGOA as well as findings and recommendations that can be implemented to assist with this issue. What this dissertation was aiming to establish was the perpetual involvement of developed countries in the affairs of developing countries. This is illustrated through the renegotiation of the AGOA in 2015, where SA had to accept ultimatums set for it by the US. This dissertation further shows that such tactics are nothing new when the US is involved, as is evidenced by its involvement in major global events that have shaped the course of history. This approach is not only harmful but also stagnates development, as developing countries must adhere to agreements that sometimes are not to their benefit. The findings indicate a contradictory pattern: when solutions to challenges faced by developing countries are presented, they translate instead into a further stronghold over developing countries because of past atrocities such as colonisation and apartheid. What appears throughout the dissertation are the ever-present structures that are intended to perform functions supposed to be for the improved good of developing countries, but which result in those countries facing never-ending challenges, some of which are self-inflicted through alliances such as the AGOA with developed countries.
Keywords: AGOA; African Growth and Opportunity Act; Developing countries; Dumping; GATT; General Agreement on Tariffs and Trade; Trade relations; WTO; World Trade Organization

Price reduction as a remedy for breach of contract by the seller under the CISG and English law - Mukuna, Nomator (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

The interruption of liquidation by business rescue application: a lacuna in the Companies Act - Ntingane, Neo Samantha (University of Johannesburg, 2019)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

The rights of illegal workers not to be unfairly dismissed, with emphasis on illegal immigrants and sex workers - Ntshalintshali, Phindile Ziningi Glenn (University of KwaZulu-Natal, 2019)
Illegal workers have been and continue to be the most vulnerable category of employees in the labour market, the reason for this is the invalidity of their employment contract due to illegality. For the longest time, the Labour Relations Act (hereinafter the LRA) has not been able to afford these workers protection because they did not fall within the ambit of the legal definition of ‘employee’ and the Act only recognises employees as holders of the rights provided for under the LRA. As a result of the Act not being able to protect these workers, they have become victims of exploitation and vicious abuse in the hands of their employers, making them vulnerable in their employment relationship. The law concerning illegal workers has since changed. Courts have found that these workers are in fact employees for the purposes of the LRA, and that, for an employment relationship to exist there need not be a valid employment contract in existence. An employment relationship may take various forms and the goal that the Labour Relations Act seeks to achieve is to protect those employees who find themselves vulnerable as a result of the illegality of their employment contract. It has also been argued that the law aims mostly at penalising the employer rather than the employee who is economically and socially weaker than the employer, therefore, courts have found that the Labour Relations Act should be interpreted in a manner that is consistent with the Constitution of the Republic of South Africa (hereinafter the Constitution) which requires a wider interpretation of who may be afforded the right to fair labour practices.
Keywords: Illegal workers; Immigrants; Sex Workers; Unfair dismissal

The rights and duties of parties to liability insurance contracts at claim stage - Ntuli, Bonginkosi (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)
Keywords: Insurance claims; Insurance policies

Business rescue: a delay tactic for liquidation? - Nxumalo, Misiwe Mpilenhle (University of KwaZulu-Natal, 2019)
No abstract provided.
Keywords: Business rescue; Company creditors; Company law; Liquidation; Shareholders

The possible impact of the Hague Convention on the recognition and enforcement of foreign judgments in civil or commercial matters on private international law in common-law West Africa - Okorley, Solomon (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The position of a director in South African Law : is it worth the risk - Raselo, Moeketsi Thebe (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Exemption clauses : contractual exclusion of delictual damages - Sande, Janet (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

An appraisal of the implementation of the retail distribution review's recommendations - Wilkins, Chanel (University of Johannesburg, 2019)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Determining the proper law of an International Funds Transfer - Yeboah, Abena Takyiwa (University of Johannesburg, 2019)
There are many ways of making payments. One of the available options for parties to international commercial transactions is international funds transfers. These transfers occur across borders and so, raise conflict of law issues. There are some laws known internationally that regulate international funds transfers. These laws include the UNCITRAL Model Law on International Credit Transfers (no country has ratified it), article 4A of the Uniform Commercial Code and the Rome I Regulation. There are diverse ways in determining which law applies to an international funds transfer. This is done either by assessing the transaction as a single transfer or as a set of linked transactions. In African countries like Ghana and South Africa, there is a gap in the approach of the law in addressing the conflict of laws issues regarding international funds transfers. This dissertation addresses the gap in these legal regimes using the present private international law as a guide. Additionally, the present legislation and legal jurisprudence are analysed, and suggestions are given as to its improvement. This author also advocates for a legislation that adequately addresses the issues raised by transnational funds transfers in these countries. Conclusively, this will promote a predictable approach in determining the applicable law in transnational funds transfers.
Keywords: Fund transfer; Transfert de fonds; Transfert international